An overview of sequential injection chromatography - Chocholous, Petr; Solich, Petr; Satínský, Dalibor (Analytica chimica acta, 2007)
New generation of sequential injection analysis (SIA) called sequential injection chromatography (SIC) has already been consolidated as a good alternative of high performance liquid chromatography (HPLC) for fast analysis of simple samples. Benefits of flow methods are automation, miniaturization and low sample and mobile phase consumption. Implementation of short monolithic chromatographic column into SIA opens new area-on-line chromatographic separation of multi-compound sample in low-pressure flow system, with the advantage of flow programming and possibility of sample manipulation. In the presented review the potential of SIC and its comparison with HPLC for determination of pharmaceutical mixtures is discussed and outlines past and recent trends focused on separation with SIC.
Keywords: lidé; Flow Injection Analysis; lékové formy; chromatografie; Chromatography; průtoková injekční analýza; Dosage Forms; Humans